Pretreatment and separation of crude glycerol from glycerol residue using membrane reactor on effect of trans membrane pressure and cross flow velocity - Muhammad Fitri, Ismail (2010)
The objective of this research is to study the effect of trans membrane pressure and cross flow velocity on flux decline during crude glycerol recovery. The crude glycerol is just the waste from oleochemical process and biodiesel industry that basically wasted. The glycerol can be recovered and potentially have many used of it by refining from transesterification process from biodiesel industry. The glycerol residue was undergoing the pre treatment process using high concentration of acid to convert to crude glycerol then followed by filtration process to remove charred substances. The neutralization process is then used to neutralize the aqueous glycerol. The 22x2 inches cylinder ceramic membrane had been used with 0.9 micron of pore size. The membrane filter had its own limitation on trans membrane pressure, time of filtrate and cross flow velocity. The result found the increasing of TMP will enhance the higher flux decline and faster to steady state. While increasing the CFV will increase the flux decline and late become steady state. The optimum CFV was 0.75 m/s with 72.22 % of flux decline. The optimum TMP was 2.5 bars with 63.88% of flux decline. The CFV give higher effluence in flux decline compared to TMP.